Parabens Removal from Domestic Sewage by Free-Floating Aquatic Macrophytes - Anjos, M. L. [UNESP]; Isique, W. D. [UNESP]; Albertin, L. L. [UNESP]; Matsumoto, T. [UNESP]; Henares, M. N. P. (Springer, 2019)
Parabens are substances that prevent or delay the deterioration of cosmetics, drugs and food caused by the action of microorganisms. Recent studies report their potential to affect human health. The present study reported the efficiency of two aquatic macrophytes (Landoltia punctata and Lemna minor) in parabens (methyl and propyl parabens) removal from domestic sewage. Two 3000-L tanks were used in the experiment: tank A, containing L. punctata; and tank B, containing L. minor. Samples were collected every three days for 21 days at daylight and evening times. The best methylparaben (MeP) removal results were recorded for tank A, 90.8 and 90.6% removal at daylight and at evening time, respectively. For propylparaben (PrP), the best removal were recorded for tank B, 88.0 and 90.5% removal at daylight and at evening, respectively. These results highlight the efficiency of polishing ponds containing aquatic macrophytes for parabens removal purposes.
Keywords: Methylparaben; Propylparaben; Lemnaceae; Duckweeds polishing ponds; Phytoremediation